2014
DOI: 10.4149/av_2014_02_128
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, host range, and distribution of tomato yellow leaf curl virus in Iran

Abstract: Summary. -Tomato yellow leaf curl virus (TYLCV) is considered one of the most important tomato pathogens in tropical and subtropical regions including Iran. During the years 2007 to 2009, a total number of 510 symptomatic and asymptomatic vegetable, ornamental and weed samples were collected from fields and greenhouses in ten provinces of Iran. Symptoms included stunting, yellowing, leaf curl and flower senescence. PCR with specific primers showed TYLCV infection in 184 samples (36%) such as cucumber, pepper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…These viruses have become a main constraint on crop production all through the world due to the worldwide increase in their population and distribution of insect vectors, and movement of plant material globally ( Seal et al, 2006 ). In the present work, the main vegetable producing areas in Khuzestan and Tehran provinces of Iran were surveyed in the period of 2012–2014 for the presence of TYLCV and the virus was found to be widespread in these regions, similar observations have been reported previously ( Bananej et al, 2009 ; Shirazi et al, 2014 ); this may reflect both a very high inoculum reservoir and the prevalence and efficiency of its whitefly vectors. This study also reports the natural occurrence of TYLCV on alfalfa, pepper and spinach plants for the first time in Iran; these hosts may play an important role in the spread of the virus in these regions.…”
Section: Discussionsupporting
confidence: 84%
“…These viruses have become a main constraint on crop production all through the world due to the worldwide increase in their population and distribution of insect vectors, and movement of plant material globally ( Seal et al, 2006 ). In the present work, the main vegetable producing areas in Khuzestan and Tehran provinces of Iran were surveyed in the period of 2012–2014 for the presence of TYLCV and the virus was found to be widespread in these regions, similar observations have been reported previously ( Bananej et al, 2009 ; Shirazi et al, 2014 ); this may reflect both a very high inoculum reservoir and the prevalence and efficiency of its whitefly vectors. This study also reports the natural occurrence of TYLCV on alfalfa, pepper and spinach plants for the first time in Iran; these hosts may play an important role in the spread of the virus in these regions.…”
Section: Discussionsupporting
confidence: 84%
“…In parallel to the growing trend in tomato cultivation, risks of crop losses due to biotic stresses have also increased over the years. Several fungal and viral diseases such as alternaria leaf spot, fusarium and verticillium vascular wilts (Amini, ), and Tomato yellow leaf curl virus (Shirazi et al ., ), have been reported to affect tomato production in the country. In contrast, no reports of economic losses due to bacterial diseases of tomato are available from Iran.…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, the incidence of infection is very high, with visual estimates of TYLCV infection reaching 100 % in some areas [12]. TYLCV epidemiology in key tomato growing areas of Iran, notably in the central and southern regions, was found to be 36%, while it was found to be 89 % in tomato fields in Saudi Arabia, which borders Iran's southern region [13]. The unexpected TYLCV outbreak in these areas could be attributed to warm weather conditions that promote vector activity, virus replication, or host susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…The unexpected TYLCV outbreak in these areas could be attributed to warm weather conditions that promote vector activity, virus replication, or host susceptibility. It has recently been revealed that The Mediterranean region and the Middle East are the key starting points for worldwide TYLCV movements [13]. Stunting, leaf curving upward, chlorosis, reduced leaf size, flower abortion, stem erect, limited plant growth and loss in tomato production are typical symptoms of TYLCV infection.…”
Section: Discussionmentioning
confidence: 99%